Behavioral and emotional functioning of children with specific learning disorders - Asarnisa Begum M,; Kandasamy V, (Asian Journal of Medical Sciences, 2024)
Background: Specific learning disorder (SLD) is distinct from other Diagnostic and Statistical Manual (DSM)-5 mental disorders as it is recognized clinically in medicine and as a separate category in special education. Aims and Objectives: The study aimed to study the behavioral patterns and emotional functioning in children with SLD. Materials and Methods: This observational cross-sectional study was conducted at Tirunelveli Medical College, Tirunelveli, from January 2019 to April 2020 on 100 patients (study group 50 and control group 50) diagnosed with SLDs as per DSM5 criteria. A patient’s history includes age, gender, symptoms, and diagnosis. Assessments were done through a semi-structured proforma, Rutter Children’s Behavior Questionnaire (parent form), the Vanderbilt attention deficit hyperactivity disorder (ADHD) diagnostic rating scale, and the Rosenberg self-esteem scale (RSES). Results: The patient’s domicile in rural areas was 82% compared to urban areas, which is 18%. The Rutter scale – total score was higher in the study group, with a mean of 3.24, compared to the control group, with a mean of 0.44. The RSES compared self-esteem scores and the mean self-esteem scores of 21.56 and 14.72, respectively (P<0.0001). The deviant/antisocial behavior subscale scores were higher for the study group, with a mean score of 1.08, than the control group, with a mean score of 0.02 (<0.05). The ADHD (inattentive type) Vanderbilt scale was compared, and it was found to be positive for the study group and none for the control group (P=0.022). Conclusion: The scores show a significant correlation between higher rates of neurotic behavior and behavioral problems, predominantly inattentive types, in SLD children.